PENGARUH FINANCIAL LITERACY DAN INVESTMENT PLATFORM TERHADAP MINAT BERINVETASI PADA PASAR MODAL SYARIAH (Studi Generasi Millenial Kota Parepare): (Studi Generasi Millenial Kota Parepare) - Wardana, Wisnu; Suarning, Suarning; Kamal Zubair, Muhammad; Semaun, Syahriyah; Muliati, Muliati (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
Investment is a component that is used as a standard for measuring economic growth in a country. The high and low level of investment in a country will greatly affect the cycle and economic activity in the country. One of the investment instruments that is increasingly in demand by the public today is the capital market, including the Islamic capital market. This is based on the phenomenon of increasing the number of investors in the Islamic capital market, especially during the Covid-19 pandemic which is dominated by millennials and z generations. The increase in the number of millennial generation investors is supported by increasing awareness of financial literacy. Another supporting factor is the development of technology and information systems that make it easier to invest in investment platforms that can be accessed on gadgets. So the purpose of this study is to provide an overview of the interest of the millennial generation of Parepare City to invest in the Islamic capital market. The influencing factors are financial literacy and investment platform as independent variables and investment interest in the Islamic capital market as a dependent variable. The research method uses quantitative descriptive research with the type of Field Research research (field research). The population in this study is the millennial generation of Parepare City, with a sample of 100 people. Based on the results of data analysis, financial literacy variables positively affect the interest of the millennial generation to invest in the capital market. The investment platform variable has a positive effect on the millennial generation's interest in investing in the Islamic capital market.